Fruiting phenology, seed and seedling morphology of Bentinckia condapanna Berry ex Roxb., an altitude specific endemic palm species of the southern Western Ghats - Reshma, M Das; Anilkumar, C; Radhamany, P M (Plant Science Today, 2025)
Bentinckia condapanna is an endemic palm of the southern Western Ghats, which holds crucial ecological impact since it is a food source for many endemic frugivorous fauna. Patchy populations confined amongst cliffy niches is a cozy sight concerning consistent demographic loss. Seeds are the sole reproductive propagules of the vulnerable species; nevertheless, few data are available regarding fruiting phenology and seed biology. The present study monitored the fruiting phenology, seed and seedling morphology of B. condapanna, which is a pre-requisite for the conservation strategies. The fruit maturation in the palm is a supra-annual process. It exhibited year-round flowering and fruiting; however, mast spadix exposure was found during the dry season and the peak fruit maturation overlapped the period between May to August. The sinuate ridged seed lodges a top-shaped embryo in the cavity beneath the operculum, proximal to the endocarpic stalk-like ridge above the hilum. The moisture content of the mature seed indicates its recalcitrant nature. The seed germination was found to be adjacent and displayed a slow erratic pattern with low germination and a prolonged dormancy period. The cotyledonary petiole emerges from the seed as a button-like structure, which later subtends the primary root and the plumular axis. Eophyll emerges from the plumular axis subsequently after the emission of a single ligule and two cataphylls. The suspected recalcitrance with dormancy nature might be the contributing factor for its low regeneration in the habitat.